Supporting parents following pregnancy loss: a cross-sectional study of telephone peer supporters. Issue 1 (December 2015) - Boyle, Frances; Mutch, Allyson; Barber, Elizabeth; Carroll, Christine; Dean, Julie
Abstract Background The death of a baby before or soon after birth can place an enormous psychological toll on parents. Parent support groups have grown in response to bereaved parents' unmet needs for support. Peer support is the hallmark of these organisations but little is known about the experiences of volunteers who provide support. This study examines the perceptions and experiences of parent support group volunteers who deliver a 24-h telephone support service for the Australian Stillbirth and Newborn Death Support (Sands) organisation in order to inform the ongoing development and sustainability of effective peer support. This parent-led organisation has delivered support to those affected by miscarriage, stillbirth and newborn death for more than 30 years. Methods Twenty-four Parent Supporters completed an online questionnaire. A mix of open- and closed questions asked about aspects of the Parent Supporter role. Quantitative data was summarised using descriptive statistics. Free-text responses to open-ended items were categorised and used to extend and illustrate the quantitative findings. Results Our findings reveal a group of highly dedicated and experienced volunteers who had taken 473 calls in the preceding 12 months. Calls were diverse but most were from bereaved mothers seeking 'to talk with someone who understands' in the early weeks and months after stillbirth or miscarriage. Most Parent Supporters indicated they felt well-prepared, confident, and satisfied in their role. Challenges include balancing the demands of the role and ongoing training and support. Conclusions Peer volunteers contribute to addressing a significant need for support following pregnancy loss. Delivering and sustaining high quality parent-led support depends on volunteer recruitment and retention and this, in turn, requires organisational responses.